Mechanisms Mediating High-Molecular-Weight Hyaluronan-Induced Antihyperalgesia - Bonet, Ivan J.M. (J Neurosci, 2020)
We evaluated the mechanism by which high-molecular-weight hyaluronan (HMWH) attenuates nociceptor sensitization, in the setting of inflammation. HMWH attenuated mechanical hyperalgesia induced by the inflammatory mediator prostaglandin E2 (PGE(2)) in male and female rats. Intrathecal administration of an oligodeoxynucleotide antisense (AS-ODN) to mRNA for cluster of differentiation 44 (CD44), the cognate hyaluronan receptor, and intradermal administration of A5G27, a CD44 receptor antagonist, both attenuated antihyperalgesia induced by HMWH. In male rats, HMWH also signals via Toll-like receptor 4 (TLR4), and AS-ODN for TLR4 mRNA administered intrathecally, attenuated HMWH-induced antihyperalgesia. Since HMWH signaling is dependent on CD44 clustering in lipid rafts, we pretreated animals with methyl-β-cyclodextrin (MβCD), which disrupts lipid rafts. MβCD markedly attenuated HMWH-induced antihyperalgesia. Inhibitors for components of intracellular signaling pathways activated by CD44, including phospholipase C and phosphoinositide 3-kinase (PI3K), also attenuated HMWH-induced antihyperalgesia. Furthermore, in vitro application of HMWH attenuated PGE(2)-induced sensitization of tetrodotoxin-resistant sodium current, in small-diameter dorsal root ganglion neurons, an effect that was attenuated by a PI3K inhibitor. Our results indicate a central role of CD44 signaling in HMWH-induced antihyperalgesia and suggest novel therapeutic targets, downstream of CD44, for the treatment of pain generated by nociceptor sensitization. SIGNIFICANCE STATEMENT High-molecular-weight-hyaluronan (HMWH) is used to treat osteoarthritis and other pain syndromes. In this study we demonstrate that attenuation of inflammatory hyperalgesia by HMWH is mediated by its action at cluster of differentiation 44 (CD44) and activation of its downstream signaling pathways, including RhoGTPases (RhoA and Rac1), phospholipases (phospholipases Cε and Cγ1), and phosphoinositide 3-kinase, in nociceptors. These findings contribute to our understanding of the antihyperalgesic effect of HMWH and support the hypothesis that CD44 and its downstream signaling pathways represent novel therapeutic targets for the treatment of inflammatory pain.